Supply chain coordination with dual procurement sources via real-option contract. (February 2015) - Luo, Meiling; Li, Gang; Johnny Wan, C.L.; Qu, Rong; Ji, Ping
Highlights: We explore the manufacturer's optimal procurement strategy under stochastic demand. The manufacturer purchases from the supplier and the existing spot markets. The manufacturer maneuvers the real-option to coordinate the supply chain. Effects of risks in the spot market on market equilibrium are derived. Abstract: In a two-stage supply chain with a supplier and a manufacturer, the manufacturer can purchase a product either from the supplier or in the spot market. The spot market, however, inevitably involves price fluctuation risk and supply risk. Assuming that the manufacturer is the leader in a procurement game and offers a real-option contract to the supplier, we study the manufacturer's optimal mixed procurement strategy that integrates the use of the real-option contract and the spot market. Moreover, we analyze the effects of the price risk and the supply risk in the spot market on market equilibrium. We show that using the real-option contract mechanism improves the overall expected profit of a supply chain and guarantees supply chain coordination in the presence of the spot market. The results also demonstrate that the price risk and the supply risk in the spot market adversely affect the manufacturer's expected profit. On the contrary, these two risks bring benefits to the supplier.